A Study of Crab (Portunus pelagicus) Peeling Household Industrial Waste in Rembang Regency and Its Potential as a Socio-Scientific Issue (SSI) Context in Science Learning - Puji Winarti; Margareta Rahayuningsih; Aditya Mariani (Universitas Negeri Semarang, 2024)
The context Socio Scientific Issue (SSI) for learning is not only a global issue. Local environmental problems have a higher relevance to students' knowledge in learning. This study aims to analyze the potential and impact of crab peelings household industry waste in Rembang Regency and its potential as a SSI context in Science Learning. A descriptive qualitative research method was used in this study. Data collection was conducted using interviews, observation, and literature study. The results showed that the waste of the crab peeling has the potential to be utilized, including as an ingredient for making petis, natural food flavors, sources of calcium and phosphorus in food, ingredients for making organic fertilizers, corrosion bio inhibitors, fish and shrimp feed, metal adsorbents, food preservatives. Crab waste that is not managed properly harms the environment and society including odor contamination, contamination of groundwater and surface water, and as a breeding ground for flies and bacteria which has a serious impact on public health. The environmental problems caused by the waste from the crab peeling household industry in Rembang Regency are controversial social problems, with no immediate solution and require consideration of various factors, such as moral, ethical, cultural, traditional, economic, political, and environmental, and require scientific understanding and community agreement for resolution. Therefore, the study of this matter has the potential to be raised as an SSI context in science learning.